(untitled) (European Journal of Pure and Applied Mathematics, 2020)
In this paper, we introduce a class of truncated tangent polynomials which generalizes tangent numbers and polynomials, and establish various properties and identities. Moreover, we obtain some interesting correlations of truncated tangent polynomials with the Stirling numbers of the second kind and with the hypergeometric Bernoulli polynomials.